A Global History of Ideas in the Language of Law - Schuppert, Gunnar Folke (Global Perspectives on Legal History, 2021)
This book argues that the narrowing focus of the global history of ideas on narratives in historical research, philosophy and political theory neglects the fact that the central concepts of the history of political ideas are articulated in the language of law. Key figures of the history of ideas, like Kant, Hegel and Weber, engaged deeply with the philosophy and sociology of law. This monograph reveals the significance of the legal semantics of the history of ideas.